Assessing the Acceptance of Pedestrian-Activated Signal System (PASS) in Malang Campus Area - Wardani, Rr. Tri Istining; Sudjanarti, Dwi; Utomo, Heru; Khabibah, Umi; Murtiyanto, Rizky Kurniawan; Akmalia, Masitha Nisa (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
Implementing the Pedestrian-Activated Signal System (PASS) as a traffic safety technology innovation requires a deep understanding of user readiness and acceptance, especially in campus environments that are dense with pedestrian activity. This research aims to analyze the influence of Technology Readiness (TR) factors consisting of Optimism, Innovativeness, Discomfort, and Insecurity and Technology Acceptance Model (TAM) factors, namely Perceived Ease of Use, Perceived Usefulness on Behavioral Intention to Use the PASS system.This research uses a quantitative approach with a survey method of 215 respondents who are campus academics and the community who use the PASS in Malang City. Data analysis techniques were carried out using SPSS software with multiple linear regression tests to see the influence of variables in the TR and TAM models that had been formulated.The research results show that Optimism, Innovativeness, Perceived Ease of Use, and Perceived Usefulness have a positive effect on Behavioral Intention to Use. Meanwhile, Discomfort and Insecurity have a negative effect on Behavioral Intention to Use. This suggests that both psychological readiness and technology perception play an important role in shaping PASS intention to use.These findings confirm that the success of PASS implementation is not only determined by the technical aspects of the system, but also by the mental readiness and perception of the user. Therefore, it is important for institutions and technology developers to prioritize education and outreach strategies that strengthen user acceptance. Thus, PASS can be used sustainably to support pedestrian safety in the campus environment.